(untitled) (Research, Society and Development, 2020)
Soil compaction and nutrient accumulation on the surface have been a major problem. Soil scarification can alter nutrient variability due to partial soil mobilization. This research aimed to evaluate by multivariate techniques the main chemical attributes of the soil that best relate to soybean yield and production components. The experiment was performed in a dystrophic Red Oxisol, in the agricultural year of 2015/16, in Savannah area located in the Selvíria County, MS, Brazil. The experiment consisted of two cultivated areas, one under no-tillage system (NTS) implemented 13 years ago and another in minimum cultivation system scarified (MCSS). Were evaluated: population of plants, first pod insertion height, plant height, the number of pods per plant, grain per plant, grain per pod, the weight of 100 grains, grain yield and soil chemical attributes. Soybean yield was higher in NTS when compared to MCSS scarified. The values of pH, calcium content, magnesium and phosphorus in the layer of 0-0.10 m, as well as the content of K in 0.10-0.20 m, are the attributes that most contributed to the increase of soybean productivity in NTS and MCSS.